About the circumscription of Celosia argentea (Amaranthaceae) and the related Linnaean taxa - Iamonico, Duilio (Phytotaxa, 2013)
As part of the revision of the genus Celosia Linnaeus (1753: 205) for the treatment of Amaranthaceae for the Euro+Med plantbase project and the New Flora of Italy (Iamonico, in prep.), it has been necessary to establish the identity of C. argentea Linnaeus (1753: 205) in comparison with the related taxa C. cristata Linnaeus (1753: 205), C. castrensis Linnaeus (1762: 297) and C. margaritacea Linnaeus (1762: 297) (Feng et al. 2009). A first step was the typification of the names (Iamonico & Jarvis 2012). Here the current circumscription of C. argentea in comparison with C. cristata, C. castrensis and C. margaritacea are discussed using relevant literature and morphological data of collections (70 specimens from the Herbaria B, BAR, FI, K, KUFS, PE, RO, LINN andTROY were examined).